2013
DOI: 10.1021/jz400108y
|View full text |Cite
|
Sign up to set email alerts
|

Negative Ion Photoelectron Spectroscopy Reveals Thermodynamic Advantage of Organic Acids in Facilitating Formation of Bisulfate Ion Clusters: Atmospheric Implications

Abstract: Recent lab and field measurements have indicated critical roles of organic acids in enhancing new atmospheric aerosol formation. Such findings have stimulated theoretical studies with the aim of understanding the interaction of organic acids with common aerosol nucleation precursors like bisulfate (HSO4(-)). We report a combined negative ion photoelectron spectroscopic and theoretical investigation of molecular clusters formed by HSO4(-) with succinic acid (SUA, HO2C(CH2)2CO2H), HSO4(-)(SUA)n (n = 0-2), along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 67 publications
5
79
1
Order By: Relevance
“…However, as for the water molecule introduced into the reaction, when the typical concentration is about 5.18 × 10 17 molecule cm −3 . the corresponding rate ratio is about 11 at 240 K. Therefore, the NH 2 + H 2 SO 4 … H 2 O reaction can complete well with the naked NH 2 + H 2 SO 4 reaction at temperatures below 240 K. The formed HSO 4 … NH 3 complex furthermore interacts with atmospheric molecules, which are involved in ion‐mediated nucleation …”
Section: Resultsmentioning
confidence: 99%
“…However, as for the water molecule introduced into the reaction, when the typical concentration is about 5.18 × 10 17 molecule cm −3 . the corresponding rate ratio is about 11 at 240 K. Therefore, the NH 2 + H 2 SO 4 … H 2 O reaction can complete well with the naked NH 2 + H 2 SO 4 reaction at temperatures below 240 K. The formed HSO 4 … NH 3 complex furthermore interacts with atmospheric molecules, which are involved in ion‐mediated nucleation …”
Section: Resultsmentioning
confidence: 99%
“…However, sulfuric acid is not abundant enough in the atmosphere to alone explain the observed formation rates of new particles (9). It remains unclear how other compounds participate, but clusters involving sulfuric acid may be stabilized by electric charge, water vapor, bases such as ammonia and amines (9)(10)(11)(12), and oxidized organics (13)(14)(15)(16). The formation of stable clusters is a distinct critical step in atmospheric new particle formation (3).…”
Section: Significancementioning
confidence: 99%
“…Sulfuric acid has been shown to be the key compound in atmospheric particle formation (see, for example, Kuang et al 5 and Sihto et al 6 ), but is not alone able to explain the formation rates observed in the troposphere. Instead, other atmospherically relevant species, such as bases and organic compounds, as well as ions, have been proposed to enhance the formation and growth of sulfuric acid-containing particles (see, for example, Zhang et al, 7 Zhang et al, 8 and Hou et al 9 ), out of which base compounds, most importantly ammonia and amines, seem to be promising candidates to take part in the first steps of cluster formation. Ammonia and dimethylamine have been theoretically shown to be capable of stabilizing sulfuric acid clusters (Kurtén et al 10 and Loukonen et al 11 ).…”
Section: Introductionmentioning
confidence: 99%